Inside Back Cover: A Combined Transition‐Metal‐Catalyzed and Photopromoted Process: Synthesis of 2, 3‐Fused 4‐Phenylnaphthalen‐1‐yl Carboxylates from 1, 7‐Diaryl‐1, 6‐diynes (Chem. Eur. J. 25/2015). Issue 25 (3rd June 2015) - Yamamoto, Yoshihiko; Mori, Shota; Shibuya, Masatoshi
<x xml:space="preserve">Abstract</x> Efficient assembly of diverse lignan‐like molecules has been achieved by a combined transition‐metal‐catalyzed and photopromoted process from 1, 7‐diaryl‐1, 6‐diynes and carboxylic acids. 2, 3‐Fused 4‐phenylnaphthalen‐1‐yl carboxylates are obtained in a step‐ and atom‐economical manner using a ruthenium‐catalyzed hydrocarboxylative cyclization and subsequent oxidative photocyclization. The diversification of the arylnaphthalene product is also possible using late‐stage CH functionalizations. For more details, see the Full Paper by Y. Yamamoto et al. on page 9093.